(untitled) (Al-Aqad, 2025)
This research aims to understand and qualify the gold savings product contract at Bank Syariah Indonesia (BSI) Ahmad Yani branch, referring to the KHES (Council of Islamic Scholars) regulations on murabahah sales. The gold savings product is a service that allows customers to buy and sell gold at affordable prices, with the facility of safekeeping. This service provides ease for the public to invest in gold. Gold savings at BSI use a murabahah contract. Generally, murabahah is a sales contract between the bank and the customer at the acquisition price plus an agreed profit margin. A qualitative research method with an empirical juridical approach was employed in this study. Primary data was collected through interviews with two informants from the BSI Ahmad Yani Pontianak branch. Secondary data was obtained from journals, articles, and the internet. Data collection techniques involved documentation and interviews. The collected data were analyzed systematically and presented in a research report.